DESIGN ANALYSIS OF MATERIAL LAYOUT IN WH02 PT. XYZ TO MINIMIZE WASTE USING CLASS BASED STORAGE POLICY - Handayani, Dwi; Rusman, Muhammad; Saputri, Irna (Journal of Industrial Engineering Management, 2024)
The business process at PT. XYZ is supported by various divisions with its own functions. One of the mentioned divisions is the Logistic division. This division manages the procurement of goods and services for the mining process. One of the subdivisions in Logistics is the warehouse. Warehouse handles incoming items and items that will be distributed to users. To meet user needs, warehouse operations must be optimized by reducing inefficient activitie. However, in reality, several problems are still found from various indications of waste that cause delays in warehouse operational processes. In this study, a waste analysis is conducted using the Waste Assessment Model to determine the percentage of each waste that occurs in warehouse activities and to identify the type of waste with the greatest impact for potential improvement. The identification results show the percentage for each type of waste, including waste overproduction 14,21%, waste inventory 15,25%, waste defect 12,41%, waste motion 13,48%, waste transportation 12,92%, waste process 17,79% and waste waiting 13,59%. Based on the results of waste identification, it was found that the waste process had the highest percentage, which is 17,79%. The root cause of the waste process occurs in the storage and retrieval processes of materials so that recommendations for improvement are given by relayout of material using the class-based storage policy. The implementation of the class-based storage method can optimize distance by 18,07%. The storage space is reduced by 10% with a reduction of rack usage by 13. Additionally, there is an 11%